A tripropylene glycol diacrylate-based polymeric support ink for material jetting - He, Yinfeng; Zhang, Fan; Saleh, Ehab; Vaithilingam, Jayasheelan; Aboulkhair, Nesma T.; Begines, Belen; Tuck, Chris J.; Hague, Richard J.M.; Ashcroft, Ian A.; Wildman, Ricky D. (Elsevier, 2017)
Support structures and materials are indispensable components in many Additive Manufacturing (AM) systems in order to fabricate complex 3D structures. For inkjet-based AM techniques (known as Material Jetting), there is a paucity of studies on specific inks for fabricating such support structures. This limits the potential of fabricating complex 3D objects containing overhanging structures. In this paper, we investigate the use of Tripropylene Glycol Diacrylated (TPGDA) to prepare a thermally stable ink with reliable printability to produce removable support structures in an experimental Material Jetting system. The addition of TGME to the TPGDA was found to considerably reduce the modulus of the photocured structure from 575 MPa down to 27 MPa by forming micro-pores in the cured structure. The cured support structure was shown to be easily removed following the fabrication process. During TG-IR tests the T5% temperature of the support structure was above 150 °C whilst the majority of decomposition happened around 400 °C. Specimens containing overhanging structures (gate-like structure, propeller structure) were successfully manufactured to highlight the viability of the ink as a support material.